Gartner Cyst Associated with Renal Agenesis and Mullerian Malformation: A Case Report - Cachon-Alpuche, Juan Carlos; Sarmiento-Haydar, Orlando Jesus; Miranda-Guillermo, Manuel Andres; Martinez, David Arsenio (British Journal of Healthcare and Medical Research, 2024)
-